Associated Factors of Anemia in Pregnant Women - Rani Yunita; Siti Aisyah; Hasbiyah Hasbiyah (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: anemia during pregnancy is a condition in which the body does not have enough healthy red blood cells. Red blood cells provide oxygen for body tissues.Objective: to determine the relationship between mothers’ knowledge, parity and adherence to taking Fe tablets and anemia in pregnant women in the work area of Kedaton Public Health Center in 2021.Methods: this study used a quantitative analytic survey research design with a cross sectional approach. The population in this study were all pregnant women who checked their pregnancy in the work area of Kedaton Public Health Center. The sample of this study was 71 respondents who were taken systematically by dividing the desired number of samples using the random sampling method. Then, the collected data were analyzed using univariate and bivariate analysis.Results: of the 71 respondents, 52.1% respondents experienced anemia. 70.4% respondents had poor knowledge and 26.9 % respondents had good knowledge (26.9%). Respondents whose parity was at risk were 47.9% and those whose parity were not at risk were 52.1%. Meanwhile, 59.2 % respondents were disobedient in consuming Fe tablets and 40.8% respondents were obedient in consuming Fe tablets.Conclusions: Based on the results of the Chi-square test on the knowledge variable, the p-value obtained was 0.036 (<α = 0.05) meaning that there is a significant relationship between knowledge and the incidence of anemia, on the parity variable the p-value obtained was 0.000 (<α = 0.05) meaning that there is a significant relationship between parity and the incidence of anemia, and on adherence in consuming Fe tablets the p-value obtained was 0.029 (<α = 0.05) meaning that there is a significant relationship between adherence in consuming Fe tablets and anemia.Suggestion: It is hoped that Kedaton Public Health Center is more active in providing counseling to midwives related to anemia. Keywords: Anemia, Knowledge, Parity, Fe Tablets